2021
DOI: 10.3390/ijerph18126330
|View full text |Cite
|
Sign up to set email alerts
|

Pollution, Inflammation, and Vaccines: A Complex Crosstalk

Abstract: The importance of pollution in determining human health is becoming increasingly clear, also given the dramatic consequences it has had on recent geopolitical events. Yet, the consequences of contamination are not always straightforward. In this paper, we will discuss the effects of different pollutants on different aspects of human health, in particular on the immune system and inflammation. Different environmental pollutants can have different effects on the immune system, which can then promote complex path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 132 publications
(131 reference statements)
0
7
0
1
Order By: Relevance
“…Lastly, emerging evidence shows that greater air pollutant exposure is associated with lower titers of neutralizing antibodies to the SARS-CoV-2 virus following vaccination [ 55 ]. Similar associations were observed with other vaccines, and it is suggested that air-pollution-induced chronic inflammation may mediate associations with vaccine efficacy [ 55 , 56 ]. We propose that epigenetics may play a role in this, regulating the increased inflammatory and decreased antibody responses.…”
Section: Epigenetic Perturbations Of Immune Pathways By Environmental...mentioning
confidence: 59%
“…Lastly, emerging evidence shows that greater air pollutant exposure is associated with lower titers of neutralizing antibodies to the SARS-CoV-2 virus following vaccination [ 55 ]. Similar associations were observed with other vaccines, and it is suggested that air-pollution-induced chronic inflammation may mediate associations with vaccine efficacy [ 55 , 56 ]. We propose that epigenetics may play a role in this, regulating the increased inflammatory and decreased antibody responses.…”
Section: Epigenetic Perturbations Of Immune Pathways By Environmental...mentioning
confidence: 59%
“…Nevertheless, we cannot limit human health solely to these factors, and the effectiveness of vaccine plays the most important role. Further studies are needed to confirm the relationship between vaccines, pollution, and their consequences [155].…”
Section: Significance Of the Results And Health Recommendationsmentioning
confidence: 99%
“…In our study, a healthy state is associated with a reduced probability of contracting the virus, which can demonstrate the importance of innate immunity; however, in no case should we base our recommendations totally on this. Nevertheless, we cannot limit human health solely to these factors, and the effectiveness of vaccines plays the most important role [ 134 ].…”
Section: Discussionmentioning
confidence: 99%